2020
DOI: 10.1108/jpmd-06-2019-0043
|View full text |Cite
|
Sign up to set email alerts
|

Place branding and local food souvenirs: the ethical attributes of national parks’ brands

Abstract: Purpose This paper aims to identify what ethical attributes tourists associate with national parks’ brands shown on food souvenir labels and the influence of such attributes on purchase motivations. Design/methodology/approach An exploratory study was carried out involving a total of 102 Italian tourists, who were interviewed at two different souvenir shops in Italy. Respondents were first asked to describe what images and values they were associating with the visited Italian National Park. The second level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…Small shops and markets could represent significant elements to support the dissemination of knowledge of local products and promote activities accordingly. Through the purchase of local food products, visitors establish a closer bond to the place and producers and keep memories of different countries and cultures (Pizzichini et al, 2020). However, in the cases observed, there was a lack of attention concerning this aspect.…”
Section: Food Market and Petty Tradementioning
confidence: 99%
See 2 more Smart Citations
“…Small shops and markets could represent significant elements to support the dissemination of knowledge of local products and promote activities accordingly. Through the purchase of local food products, visitors establish a closer bond to the place and producers and keep memories of different countries and cultures (Pizzichini et al, 2020). However, in the cases observed, there was a lack of attention concerning this aspect.…”
Section: Food Market and Petty Tradementioning
confidence: 99%
“…R.K. -Director of Musselfest organizing committee As it emerged in the interviews, this approach might have a negative impact on place identity and the tourists' perception of food authenticity. Several studies found that local origin and authenticity of food products are important factors for tourists who desire to explore the local culture, to obtain unique products and to contribute to the local community development (Pizzichini et al, 2020;Altintzoglou et al, 2016;Sims, 2009;Sthapit, 2018).…”
Section: Food Market and Petty Tradementioning
confidence: 99%
See 1 more Smart Citation
“…It is expected that the model creates added value for historic districts and influence the task of regeneration. Place/ nation branding has been discussed not only in relation to tourism destinations but also in its application to national parks (Pizzichini et al, 2020) and the food industry (Donner et al, 2017). In particular, sport mega-events are catalysts for nation branding as they create unique opportunities for transformational development and global appeal while support internal brand building and public diplomacy (Knott et al, 2017).…”
Section: Coordination Of Brand Development Activitiesmentioning
confidence: 99%
“…Some food products are closely associated with particular geographical places and countries (even if not specific to only them), and, thus, it is natural to expect from these products reflectance of the local/regional/national geographical names, i.e., their contribution to place branding. The relevant ideas are actively discussed by the contemporary researchers, and some general thoughts can be found, particularly, in the works by Blichfeldt and Halkier [1], Bosco [2], Del Casino [3], Harner [4], Lopes et al [5], Pizzichini et al [6], and Sanz-Cañada and Muchnik [7]. As shown by Merle et al [8], geographical indications influence strongly on food perceptions [8].…”
Section: Introductionmentioning
confidence: 99%